Analisis Bakteri Total Coliform dan Escherichia Coli pada Air Bersih di Lingkungan Universitas Islam Indonesia Menggunakan Media Chromogenic Coliform Agar - Rina Isnikarita; Nida Zulfah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Water is an essential element for the life of all living things. As a natural resource, water provides many benefits and influences many activities. In order to maintain a water supply, good sanitation is required and the water must be free from total coliform and Escherichia coli contamination to be safe for use. The research was conducted at the Environmental Biotechnology Laboratory, Department of Environmental Engineering, Faculty of Civil Engineering and Planning, Islamic University of Indonesia in November 2023 - December 2023. The sample in this research is the water supply found in the environment of the Islamic University of Indonesia, which includes 4 faculties (FTSP, FK, FTI, FH) and the Rectorate. This research uses the Chromogenic Coliform Agar (CCA) membrane filter media method. More than 50% of the test samples in the UII environment contained Escherichia coli, so these results indicated that the groundwater around the test site was contaminated with Escherichia coli bacteria.